The Relationship Between Work Posture and Musculoskeletal Disorders in Pottery Craftsmen (Study in Gedangan Village, Maduran District, Lamongan Regency) - Wamufiidah, Yusriiyahna; Zufra Inaya (LPPM Universitas Mohammad Husni Thamrin, 2026)
The WHO (2022) reports that 1.71 billion people worldwide suffer from musculoskeletal disorders (MSDs), contributing to 17% of Years Lived with Disability (YLDs). MSD risk is higher among informal sector workers, including pottery artisans. Preliminary surveys and local health worker information show 60% of pottery artisans in Gedangan Village experience lower back and neck pain. Objective: To analyze the relationship between work posture and musculoskeletal disorders among pottery artisans in Gedangan Village, Maduran District, Lamongan Regency. Methods: Quantitative observational analysis using a cross-sectional approach on 92 pottery craftsmen. The Rapid Upper Limb Assessment (RULA) method and Nordic Body Map (NBM) questionnaire were used, tested using Kendall's Tau statistics. Results: Most craftsmen had work postures with high ergonomic risk (84.78%). 84.74% were in the high-risk category (RULA score 7). Nearly half of musculoskeletal disorders were at moderate risk (45.7%), with most complaints in the left leg (95.65%), buttocks (94.57%), and waist (93.48%). Kendall's Tau test yielded a coefficient of -0.433 with p=0.000 (p < 0.05), indicating a significant relationship between work posture and musculoskeletal disorders. Conclusion: There is a significant relationship between work posture and musculoskeletal disorders in pottery craftsmen, requiring efforts to improve work posture, stretching education, and rest time management.